El Psicodiagnóstico de Rorschach como instrumento evaluador de grupos: un estudio de 1,200 casos - Ráez de Ramírez, Matilde (1986)
The present study tries to demonstrate the utility of the Rorschach Psychodiagnostic Test as an instrument that permits to assess personlality ( quantitatively and qualitatively) in specific groups. The test was administered to 1200 subjects of both sexes between 19 and 38 years that were requesting admission to an Institution or work promotion. The content analisis shows similarities and differences between groups according to sex, age and cultural leve!, which seems to identify more differences.